Halal Lifestyle: How Does Islamic Financial Literacy and Halal Literacy Encourage It? - Guntoro, Dibyo Waskito; Sholekhah, irmadatus; Solikin, Asep (Universitas Airlangga, 2025)
The global expansion of the Halal market highlights the growing adoption of a Halal Lifestyle, yet a persistent gap exists between Muslim consumers' intentions and their actual purchasing behavior. This study addresses a critical gap in halal consumption literature by examining how Islamic Financial Literacy (IFL) and Halal Literacy (HL) jointly influence Halal Lifestyle adoption. While previous research emphasizes religiosity, it overlooks the role of specific knowledge domains in bridging the